Are the Normative Values of Sensorineural Acuity Level (SAL) Test Affected by Head Circumferences of Subjects? (International Journal of Statistics in Medical Research, 2022)
Introduction: Sensorineural acuity level (SAL) test is believed to be helpful in estimating bone conduction thresholds in masking dilemma cases. However, before the SAL normative data can be used in clinical settings, there is a need to study the fundamental variable related to SAL normative data such as head circumference. As such, the purpose of the current study was to compare SAL normative values between subjects with bigger and smaller head circumferences at different frequencies.Materials and Methods: In this study, 48 healthy Malaysian adult subjects (aged between 18 and 50 years) were enrolled. Pure tone audiometry (PTA) and SAL test were subsequently conducted based on the recommended protocols. The SAL normative values were then compared between subjects with bigger and smaller head circumferences. Data analysis methods included paired t-test, effect size, and Bayesian approach.Results: No significant differences were noted in the SAL results when the two groups were compared, implying that the SAL normative data were not influenced by the head circumference (p > 0.05, BF10 = 0.232-0.708).Conclusions: Based on the findings of this study it appears that the SAL test results are not affected by the head sizes of the subjects. Future SAL test studies may use the normative SAL values established in the current study as a guide.